Novel homozygous variants in TTC12 cause male infertility with asthenoteratozoospermia owing to dynein arm complex and mitochondrial sheath defects in flagella - Meng, Lanlan; Liu, Qiang; Tan, Chen; Xu, Xilin; He, Wenbin; Hu, Tongyao; Tu, Chaofeng; Li, Yong; Du, Juan; Zhang, Qianjun; Lu, Guangxiu; Fan, Li-Qing; et al. (Frontiers in Cell and Developmental Biology, 2023)
The genetic causes for most male infertility due to asthenoteratozoospermia remain unclear. To identify deleterious variants in TTC12 in a large cohort of infertile Chinese males with asthenoteratozoospermia. A total of 314 unrelated asthenoteratozoospermia-affected men were recruited for whole exome sequencing. The effects of the identified variants were evaluated by in silico analysis and confirmed by in vitro experiments. Intracytoplasmic sperm injection (ICSI) was used to evaluate the efficiency of ART therapy. Novel homozygous TTC12 variants (c.1467_1467delG (p.Asp490Thrfs*14), c.1139_1139delA (p.His380Profs*4), and c.1117G>A (p.Gly373Arg), respectively) were identified in three (0.96%) of the 314 cases. Three mutants were suspected to be damaging using in silico prediction tools, and were further confirmed by in vitro functional analysis. H&E staining and ultrastructural observation of the spermatozoa revealed multiple morphological abnormalities of flagella with the absence of outer dynein arms (ODAs) and inner dynein arms (IDAs). Notably, significant mitochondrial sheath (MS) malformations were also observed in the sperm flagellar. Immunostaining assays indicated that TTC12 present throughout the flagellum of control spermatozoa. However, spermatozoa from TTC12-mutated individuals exhibited an absence staining intensity of TTC12 and ODA and IDA components. Three men accepted ICSI treatment using their ejaculated spermatozoa, and two female partners successfully delivered healthy babies. Our findings provided direct genetic evidence that homozygous variants in TTC12 cause male infertility with asthenoteratozoospermia owing to dynein arm complex defects and MS malformations in the flagellar axoneme. We also demonstrated that TTC12 deficiency-mediated infertility could be overcome by ICSI technology.